Impact of Cenozoic strike‐slip tectonics on the evolution of the northern Levant Basin (offshore Lebanon). Issue 11 (11th November 2014) - Ghalayini, Ramadan; Daniel, Jean‐Marc; Homberg, Catherine; Nader, Fadi H.; Comstock, John E.
Abstract Sedimentary basins adjacent to plate boundaries contain key tectonic and stratigraphic elements to understand how stress is transmitted through plates. The Levant Basin is a place of choice to study such elements because it flanks the Levant Fracture System and the Africa/Anatolia boundary. This paper uses new high‐quality 3‐D seismic reflection data to unravel the tectonic evolution of the margin of this basin during the Cenozoic, the period corresponding to the formation of the Levant Fracture System, part of the Africa/Arabia plate boundary. Four major groups of structures are identified in the interpreted Cenozoic units: NW‐SE striking normal faults, NNE‐SSW striking thrust‐faults, ENE‐WSW striking dextral strike‐slip faults, and NNE trending anticlines. We demonstrate that all structures, apart of the NW‐SE striking normal faults, are inherited from Mesozoic faults. Their reactivation and associated folding started during the late Miocene prior to the Messinian salinity crisis due to a NW‐SE compressional stress field. No clear evidence of shortening at present‐day offshore Lebanon and no large NNE‐SSW strike‐slip faults parallel to the restraining bend are found indicating that the Levant Fracture System is mainly contained onshore at present day. The intermittent activity of the interpreted structures correlates with the two stages of Levant Fracture System movement during late Miocene and Pliocene. This paper provides a good example of the impact of the evolution of plate boundaries on adjacent basins and indicates that any changes in the stress field, as controlled by the plate boundary, will affect immediately the preexisting structures in adjacent basins.